2012
DOI: 10.2310/8000.2011.110523
|View full text |Cite
|
Sign up to set email alerts
|

Ontario children have outgrown the Broselow tape

Abstract: Objective: The Broselow Pediatric Emergency Tape (Armstrong Medical Industries, Inc., Lincolnshire, IL) (BT) is a wellestablished length-based tool for estimation of body weight for children during resuscitation. In view of pandemic childhood obesity, the BT may no longer accurately estimate weight. We therefore studied the BT in children from Ontario in a large recent patient cohort. Methods: Actual height and weight were obtained from an urban and a rural setting. Children were prospectively recruited betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 15 publications
1
22
0
1
Order By: Relevance
“…Despite periodic revisions to the tape based on updated census data, there is evidence that as obesity rates increase, the Broselow tape may increasingly underestimate weights (7,8). Conversely, malnutrition or endemic disease burdens in certain populations may result in overestimation of weight by using the Broselow tape.…”
Section: Introductionmentioning
confidence: 95%
“…Despite periodic revisions to the tape based on updated census data, there is evidence that as obesity rates increase, the Broselow tape may increasingly underestimate weights (7,8). Conversely, malnutrition or endemic disease burdens in certain populations may result in overestimation of weight by using the Broselow tape.…”
Section: Introductionmentioning
confidence: 95%
“…28,29 Conversely, studies from more economically developed countries have found that the BT tends to underestimate weight among paediatric populations. 5,15,25,31,32 These contradictory data may reflect the increasing prevalence of obesity in more developed countries. 15,16 The strengths of the current study include its large sample size and the collection of data from a tertiary care centre which receives referrals from all over the country.…”
Section: Discussionmentioning
confidence: 98%
“…5,15,25,31,32 These contradictory data may reflect the increasing prevalence of obesity in more developed countries. 15,16 The strengths of the current study include its large sample size and the collection of data from a tertiary care centre which receives referrals from all over the country. Therefore, the subjects included in this study may be considered representative of the general Omani paediatric population.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A study conducted in India revealed that the rate of accuracy within 10% of measured weight ranges from 33.5% to 52.6% 13. Additionally, some studies have demonstrated that the Broselow tape is not appropriate across different nations and races 1 9 22 28. In contrast, other studies have determined that the Broselow tape is acceptable when ethnicity is taken into account 24 25.…”
Section: Discussionmentioning
confidence: 99%